Capacity Enhancement in Aeronautical Channels by MIMO Technology - Moazzami, Farzad (International Foundation for Telemetering, 2011)
ITC/USA 2011 Conference Proceedings / The Forty-Seventh Annual International Telemetering Conference and Technical Exhibition / October 24-27, 2011 / Bally's Las Vegas, Las Vegas, Nevada === This paper shows how the application of MIMO (multiple-input multiple-output) communication methods can enhance telemetry systems. The main contribution of MIMO to the communication systems is improving spectral efficiency by exploiting spatial diversity of multiple antennas. For communications using high order QAM modulated signals, a blind MIMO equalizer is proposed in earlier works. In this work the possibility of adapting blind MIMO equalizer to iNET problems is explored. In addition, MIMO equalization is adapted to operate as a successive interference cancellation (SIC) scheme to improve the quality of received signal in a high interference environment by capturing and cancelling the interferer.